2016
DOI: 10.4314/ahs.v16i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the recommendation of the Human Papillomavirus vaccine by South African doctors working in a tertiary hospital

Abstract: Background: In South Africa, HPV vaccination programme has been incorporated recently in the school health system. Since doctors are the most trusted people regarding health issues in general, their knowledge and attitudes regarding HPV infections and vaccination are very important for HPV vaccine program nationally. Objective: The objective of this study was to investigate factors contributing to recommendation of HPV vaccines to the patients. Methods: This was a quantitative cross-sectional study conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Similar to Hoque et al study among South African doctors, our findings show the HCPs have a general understanding of the HPV mode of transmission and its health implications [35]. Our study showed the HCPs have some basic knowledge about the HPV vaccination but there were varied views and concerns about the recommended age eligibility for vaccination, the availability, efficacy, and the safety of the vaccine.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to Hoque et al study among South African doctors, our findings show the HCPs have a general understanding of the HPV mode of transmission and its health implications [35]. Our study showed the HCPs have some basic knowledge about the HPV vaccination but there were varied views and concerns about the recommended age eligibility for vaccination, the availability, efficacy, and the safety of the vaccine.…”
Section: Discussionsupporting
confidence: 86%
“…However, it seems that their knowledge regarding HPV and its vaccine does not always match with their profession. For example, a study conducted among South African doctors [16] found that the knowledge level of HPV infections was low, and they had poor awareness about HPV and HPV vaccines. Similar results were obtained with doctors in Canada [17], India [15], and China [18].…”
Section: Introductionmentioning
confidence: 99%
“…The main finding in these papers was that PEP was underused, and it was speculated that this was partly due to the low level of PEP-related knowledge. Forty-eight questions were about different types of vaccines; 23 on hepatitis B [39][40][41][42][43], eight on human papilloma virus [44][45][46], three on influenza [47,48] viruses, and 14 questions on adverse events following immunization [49]. Questions were about overall awareness of different types of vaccines, and the effectiveness, what comprised a dose/full course, how long the vaccines offered protection, and about the safety of vaccination, adverse reactions after immunization, and medication used to prevent/relieve vaccinationrelated immune reaction.…”
Section: Disease Focusmentioning
confidence: 99%